The Development of ProBSTAD Teaching Materials With Conservation Vision on the Learning of the Nervous System in MA - Hanifah, Ishfi Zakiyatul; Lisdiana, Lisdiana; Nugrahaningsih, Nugrahaningsih (Journal of Biology Education, 2019)
ProBSTAD teaching materials have the advantage of presenting learning objects in a concrete manner so that it is good to add to the learning experience. The scientific approach links learning the material with everyday life. The nervous system material is closely related to the real life of living things. This study aims to develop ProBSTAD teaching materials with conservation vision with valid, feasible and effective criteria. This research was carried out at MA Nurul Islam Kriyan. The research subjects consisted of 37 students. The results showed the validation scores by the media and material experts were 92% and 94% with very valid criteria. The results of teacher and student responses were obtained on average 94% and 755 with very good and good criteria. Cognitive learning outcomes of students with N-gain obtained an average of 0.76 with high criteria for planting attitudes of class XI students obtained an average score of 84% in very high criteria. Based on the results of the study, it can be concluded that the teaching material of ProBSTAD with conservation vision has been valid, feasible, and effectively applied to the learning of nervous system material in MA.